Peran Pendidikan dan Pelatihan terhadap Peningkatan Kualitas Sumber Daya Manusia dengan Pemberdayaan Masyarakat sebagai Variabel Intervening - Nabila Nur Fadilah; Sutrisno Sutrisno; Efriyani Sumastuti (Jurnal Simki Postgraduate, 2025)
This study aims to examine the extent to which education and training contribute to enhancing the quality of human resources (HR), with community empowerment serving as an intervening variable. A descriptive quantitative approach was employed using a census method. Data were collected through a questionnaire designed to capture public perceptions regarding the implementation of education, training, community empowerment, and the quality of human resources. The data analysis was conducted using the Partial Least Square (PLS) method with the assistance of the SmartPLS 3 software. The findings reveal that education has a positive and significant effect on both human resource quality and community empowerment. Similarly, training shows a significant impact on community empowerment. However, community empowerment does not exhibit a statistically significant influence on human resource quality. Indirect effects are only significant along the pathway connecting education, training, and community empowerment. Furthermore, the Importance-Performance Map Analysis (IPMA) identifies education indicators as having the strongest influence on HR quality. Nevertheless, the performance level of these indicators remains moderate, indicating a need for improvement. Based on these results, it is recommended to enhance the quality of education and training programs, along with conducting a comprehensive evaluation of community empowerment strategies to support sustainable human resource development.